Liquid flows induced in a rotating drum with different fill ratios - Daeun Lee; Jaebeen Lee; Seok Min Choi; Sangtak Lee; Hyungmin Park (Scientific Reports)
Abstract In the present study, we experimentally investigate the liquid flow induced in a rotating drum (cylindrical tank with a short aspect ratio) aligned horizontally, focusing on the variation in the time-averaged and fluctuating flow structures with different fill ratios. For each fill ratio, controlled by varying the water height, we measure the velocity fields at different cross-sectional planes with particle image velocimetry while varying the rotational speed of the drum. Compared to the condition of a fill ratio of 1.0, in which the liquid inside the drum rotates forming a large-scale (solid-body rotation) organized flow structure, a substantial asymmetric flow structure shows up in partially-filled conditions driven by the imbalance between (i) the momentum diffusion along the radial direction and the centrifugal acceleration, and (ii) the downward (gravitational) flux of the induced flow. In addition to the mean flow structure, we examine the fluctuating velocity fields together with the dynamics of the free surface, and we also briefly discuss the difference between the liquid flow and granular (particle) flow in a partially-filled drum. We think that the present results provide valuable insights on the partially-filled liquid drum toward various engineering applications.